Regulation of insurance activities in Russia - M. Kh. Tsoloev (Путеводитель предпринимателя, 2020)
In this article, state regulation of insurance activity is aimed at the formation and development of an efficiently functioning insurance services market, protection of the rights and legitimate interests of all subjects of insurance relations.